Untargeted metabolomics and quantification analysis reveal the shift of chemical constituents between instant dark teas individually liquid-state fermented by Aspergillus cristatus, Aspergillus niger, and Aspergillus tubingensis - Liao, Si-yu; Zhao, Yi-qiao; Jia, Wen-bao; Niu, Li; Bouphun, Tunyaluk; Li, Pin-wu; Chen, Sheng-xiang; Chen, Wei; Tang, Dan-dan; Zhao, Yue-ling; Zou, Yao; Zhu, Ming-zhi; et al. (Frontiers in Microbiology, 2023)
Instant dark teas (IDTs) were individually liquid-state fermented using the fungi Aspergillus cristatus, Aspergillus niger, and Aspergillus tubingensis. To understand how the chemical constituents of IDTs were affected by the fungi, samples were collected and measured by liquid chromatography-tandem mass-tandem mass spectrometry (LC-MS/MS). Untargeted metabolomics analysis revealed that 1380 chemical constituents were identified in positive and negative ion modes, and 858 kinds of chemical components were differential metabolites. Through cluster analysis, IDTs were different from the blank control, and their chemical constituents mostly included carboxylic acids and their derivatives, flavonoids, organooxygen compounds, and fatty acyls. And the metabolites of IDTs fermented by A. niger and A. tubingensis had a high degree of similarity and were classified into one category, which showed that the fungus used to ferment is critical to the formation of certain qualities of IDTs. The biosynthesis of flavonoids and phenylpropanoid, which involved 9 different metabolites such as p-coumarate, p-coumaroyl-CoA, caffeate, ferulate, naringenin, kaempferol, leucocyanidin, cyanidin, and (-)-epicatechin, were significant pathways influencing the quality formation of IDTs. Quantification analysis indicated that the A. tubingensis fermented-IDT had the highest content of theaflavin, theabrownin, and caffeine, while the A. cristatus fermented-IDT had the lowest content of theabrownin, and caffeine. Overall, the results provided new insights into the relationship between the quality formation of IDTs and the microorganisms used in liquid-state fermentation.